2020
DOI: 10.1097/jsm.0000000000000795
|View full text |Cite
|
Sign up to set email alerts
|

Professional Athletes Have Poorer Sleep Quality and Sleep Hygiene Compared With an Age-Matched Cohort

Abstract: Objective: To study sleep quality and sleep hygiene in professional athletes and an age-matched cohort. Design: Cross-sectional study. Setting: Professional athletes and a sport medicine center. Participants: Professional rugby, netball and football athletes (n = 184) and attendees to a sport medicine center (n = 101). Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…It is also necessary to highlight that professional athletes report poorer sleep quality and hygiene than an age-matched cohort of non-athletes. 54 Thus, the presence of chronic sleep-related problems may represent a barrier to the potential beneficial effects of napping on physical performance.…”
Section: Daytime Napping and Physical Performancementioning
confidence: 99%
“…It is also necessary to highlight that professional athletes report poorer sleep quality and hygiene than an age-matched cohort of non-athletes. 54 Thus, the presence of chronic sleep-related problems may represent a barrier to the potential beneficial effects of napping on physical performance.…”
Section: Daytime Napping and Physical Performancementioning
confidence: 99%
“…Sleep disorders have become increasingly prevalent, it has been estimated that at least one in every five adults suffers from chronic sleep problems [2,3]. Sleep disturbances have not only become frequent in the general population, but recent studies indicate that elite athletes are faced by multiple sleep problems [1,[4][5][6][7][8]. They are known to get less sleep than non-athletes, and furthermore they have longer sleep latency and lower sleep efficiency for example because of recurrent awakenings at nighttime.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, little is known about sleep and possible challenges in sleeping at different stages of athletic career [12,15,16]. Several studies have demonstrated that professional athletes are facing increased risk of poor sleep and even sleep disorders are not uncommon among them [1,[4][5][6][7][8]. On the other hand, previous studies have also demonstrated that systematic sleep counselling can enhance the quality of athletes' sleep [1,10,17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Halson and colleagues (2022) demonstrated the impact of individual sleep behaviors on insomnia-related characteristics in a sample of professional athletes across four sports (netball, Australian rules football, rugby league, and soccer), whereby persons with irregular sleep schedules had significantly lower SE, relative to those with regular sleep schedules [ 64 •]. This may be a particularly focal contributing factor to insomnia-related characteristics in professional athletes, as Cameron and colleagues (2021) evidenced worse sleep behaviors (schedule irregularity and maladaptive sleeping environments) in professional athletes, relative to and age-matched non-athlete cohort, which also coincided with significantly more general sleep disturbances [ 60 ].…”
Section: Common Sleep Problems In Professional Athletesmentioning
confidence: 99%
“…We identified eight pieces of literature that pertain to the influence of competition factors on sleep health in professional athletes [55,60,62,[74][75][76][77][78][79]. In a sample of professional athletes across rugby, netball, and soccer, Cameron and colleagues (2021) evidenced the perception of significant, negative effects of competition on sleep [60]. 68.5% of the sample reported having difficulties sleeping after a competition.…”
Section: Competition Factorsmentioning
confidence: 99%